2006
DOI: 10.1121/1.2401193
|View full text |Cite
|
Sign up to set email alerts
|

On the potential limitations of conventional sound metrics in quantifying perception of nonlinearly propagated noise

Abstract: The use of conventional metrics to quantify the perception of nonlinearly propagated noise has been studied. Gaussian noise waveforms have been numerically propagated both linearly and nonlinearly, and from the resulting waveforms, several metrics are calculated. These metrics are overall, A-, C-, and D-weighted sound pressure levels, perceived noise level, Stevens Mark VII perceived loudness, Zwicker loudness, and sharpness. Informal listening demonstrations indicate that perceived differences in annoyance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…(An example is the so-called "crackle" phenomenon, which has instead been described using the statistics of the time waveform 1 and more recently, the time waveform derivative. 2 ) The results of the Gee et al 3 study prompted further investigation to identify a metric that objectively quantifies the perceptual differences between the nonlinearly propagated signal and a signal with equivalent long-term spectrum, or, similarly, between a crackling waveform and one that has the same spectrum. After publication of the previous study, 3 it was suggested to the authors that a more suitable metric might be TVL, which incorporates both temporal and spectral features of loudness into the model.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…(An example is the so-called "crackle" phenomenon, which has instead been described using the statistics of the time waveform 1 and more recently, the time waveform derivative. 2 ) The results of the Gee et al 3 study prompted further investigation to identify a metric that objectively quantifies the perceptual differences between the nonlinearly propagated signal and a signal with equivalent long-term spectrum, or, similarly, between a crackling waveform and one that has the same spectrum. After publication of the previous study, 3 it was suggested to the authors that a more suitable metric might be TVL, which incorporates both temporal and spectral features of loudness into the model.…”
Section: Introductionmentioning
confidence: 98%
“…2 ) The results of the Gee et al 3 study prompted further investigation to identify a metric that objectively quantifies the perceptual differences between the nonlinearly propagated signal and a signal with equivalent long-term spectrum, or, similarly, between a crackling waveform and one that has the same spectrum. After publication of the previous study, 3 it was suggested to the authors that a more suitable metric might be TVL, which incorporates both temporal and spectral features of loudness into the model. Thus, it was hypothesized that the model would respond more appropriately to the temporal features of the acoustic shocks.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is a startling staccato of cracks and bangs and its onomatope, 'crackle,' conveys a subjectively accurate impression." This sound quality-interesting to Ffowcs Williams because of its capacity to produce annoyance-cannot be identified by examination of the long-term spectral magnitude alone or any metric derived therefrom, as shown by Gee et al (2007b). It is instead "caused by groups of sharp compressions in association with gradual expansions" as noted by Ffowcs Williams et al (1975).…”
Section: Introductionmentioning
confidence: 99%